Research on the main methods and schemes of encryption with search capability - Yesin, V.I.; Vilihura, V.V. (Radiotekhnika, 2022)
The growing popularity of data outsourcing to third-party cloud servers causes their owners to have serious concerns about their security due to possible data leakage. A well-known measure to solve this problem and ensure the confidentiality of data is to encrypt it. However, the use of traditional encryption techniques is faced with the problem of how to allow untrusted cloud servers to perform search operations, while the actual data transmitted must remain confidential. Searchable encryption is a powerful tool, a class of cryptographic techniques that attempts to solve this problem. Searchable encryption acts as a data management technique that allows data owners to store and manage their data on a third-party, untrusted cloud server, and allows the data user to delegate search functions to the cloud server to retrieve that data. Currently, there are a number of approaches to solving this problem, although there is still no dominant solution. Therefore, the paper presents an overview of current secure search solutions. The main searchable encryption techniques are considered, which allow you to perform search operations on encrypted data without disclosing any information about what is being searched. The strengths and weaknesses of the analyzed methods are highlighted. Models and architectures of existing secure search engines are analyzed, taking into account the peculiarities of their operation scenarios. The problem of confidentiality in searchable encryption schemes is discussed. A comparative analysis of the performance of several searchable symmetric encryption schemes is given. Various gaps in the area under consideration are identified, with indication of open research problems.